Core Damage Quick Assessment for NPP in China. (September 2017) - Liu, Yuanyuan; Yue, Huiguo; Zhang, Shaojun; Ma, Shuai; Hongbo Jin, and
Abstract: Early emergency response for nuclear accidents is one of the effective ways to mitigate the accident consequences. In 2014, IAEA proposed a method for the evaluation results of core damage. In this paper, we review this method and a design for a national quick core damage assessment method is proposed for NPPs in operation and under construction in China. This design is based on the current core damage assessment methods in China and worldwide.